GAMBARAN PENGETAHUAN HYGIENE DAN SANITASI TERHADAP SKABIES DI PESANTREN DARUZZAHIDIN DESA LAMCEU KECAMATAN KUTA BARO KABUPATEN ACEH BESAR - Isfanda Isfanda; Yuni Rahmayanti (Jurnal Sains Riset, 2021)
Scabies is a skin disease caused by sarcoptes scabiei, and its transmission may occur in direct skin contact to the skin or indirect contact. This research is descriptive and aims to know the description of knowledge of hygiene and  sanitation  on  scabies in  daruzahidin boarding  school desa  lamceu  kecamatan Kuta Baro Kabupaten Aceh Besar. Data collection was conducted on 87 in March to June 2017 at boarding school daruzzahidin desa lamceu kecamatan kuta baro kabupaten Aceh Besar. The data collected shows that most respondents are 16 years old ( 44,8%)   the majority are female, which is also accounted for 52 people (59,1%). The results show that most respondents’ knowledge of hygiene and sanitation on scabies are in good category, (50,6 %). The author suggests to Aceh Provincial Health Office to strive to increase counseling services particularly about scabies.Keyword: knowledge, hygiene and sanitation, scabies